Orthogonal chemical functionalization of patterned gold on silica surfaces - Palazon, Francisco; Léonard, Didier; Le Mogne, Thierry; Zuttion, Francesca; Chevalier, Céline; Phaner-Goutorbe, Magali; Souteyrand, Éliane; Chevolot, Yann; Cloarec, Jean-Pierre (Beilstein Journal of Nanotechnology, 2015)
Single-step orthogonal chemical functionalization procedures have been developed with patterned gold on silica surfaces. Different combinations of a silane and a thiol were simultaneously deposited on a gold/silica heterogeneous substrate. The orthogonality of the functionalization (i.e., selective grafting of the thiol on the gold areas and the silane on the silica) was demonstrated by X-ray photoelectron spectroscopy (XPS) as well as time-of-flight secondary ion mass spectrometry (ToF–SIMS) mapping. The orthogonal functionalization was used to immobilize proteins onto gold nanostructures on a silica substrate, as demonstrated by atomic force microscopy (AFM). These results are especially promising in the development of future biosensors where the selective anchoring of target molecules onto nanostructured transducers (e.g., nanoplasmonic biosensors) is a major challenge.
Keywords: characterization; self-assembled monolayer; surface functionalization; ToF–SIMS; XPS